2015
DOI: 10.1016/j.molimm.2015.07.028
|View full text |Cite
|
Sign up to set email alerts
|

CD100 and plexins B2 and B1 mediate monocyte-endothelial cell adhesion and might take part in atherogenesis

Abstract: Leukocyte migration is essential for the function of the immune system. Their recruitment from the vessels to the tissues involves sequential molecular interactions between leukocytes and endothelial cells (ECs). Many adhesion molecules involved in this process have already been described. However, additional molecules may be important in this interaction, and here we explore the potential role for CD100 and plexins in monocyte-EC binding. CD100 was shown to be involved in platelet-endothelial cell interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 37 publications
0
38
0
2
Order By: Relevance
“…26 HUVEC were grown to 80% confluency in specific petridishes and treated with drugs as indicated in the results under flow conditions by the introduction of mechanical-sheer stress (125 dynes/cm 2 ) as described earlier. 27 Thereafter cells were washed twice with fresh media and incubated with monocytes (THP1) pretreated with 2.5 μmol/L Calcein AM for 1 hour.…”
Section: Detection Of Monocyte Adhesionmentioning
confidence: 99%
“…26 HUVEC were grown to 80% confluency in specific petridishes and treated with drugs as indicated in the results under flow conditions by the introduction of mechanical-sheer stress (125 dynes/cm 2 ) as described earlier. 27 Thereafter cells were washed twice with fresh media and incubated with monocytes (THP1) pretreated with 2.5 μmol/L Calcein AM for 1 hour.…”
Section: Detection Of Monocyte Adhesionmentioning
confidence: 99%
“…This finding was corroborated by a study by Luque et al that demonstrated that monocytes are retained on endothelial cells via the Sema4D-Plexin B1 axis [85]. In human samples of carotid artery plaques, the expression of Sema4D was enhanced, yet incubation with Sema4D reduced the formation of foam cells [85]. These studies point to a potential role of semaphorin-plexin interactions during the development of atherosclerotic lesions.…”
Section: Neuronal Guidance Proteins In Atherosclerosismentioning
confidence: 61%
“…Sema3E is upregulated in the macrophages of advanced plaques and acts as a negative regulator of macrophage migration, promoting macrophage retention and chronic inflammation [84]. This finding was corroborated by a study by Luque et al that demonstrated that monocytes are retained on endothelial cells via the Sema4D-Plexin B1 axis [85]. In human samples of carotid artery plaques, the expression of Sema4D was enhanced, yet incubation with Sema4D reduced the formation of foam cells [85].…”
Section: Neuronal Guidance Proteins In Atherosclerosismentioning
confidence: 84%
“…Essa proteína é encontrada como um dímero ligado à membrana no tamanho de 150 kDa (por subunidade) ou na forma solúvel no tamanho de 120 kDa (sCD100), obtida por clivagem (BASILE et al, 2007;ELHABAZI et al, 2003;ZHU et al, 2007). Essa clivagem é feita em plaquetas por uma metaloprotease ADAM17 (ZHU, 2007 (MOREAUFAUVARQUE et al, 2003), em crescimento e angiogênese tumorais (BASILE et al, 2006;CH'NG;KUMANOGOH, 2010;GABROVSKA et al, 2011;KATO et al, 2011;SIERRA et al, 2008;SOONG et al, 2011;YANG et al, 2011), em osteogênese (NEGISHI-KOGA et al, 2011) e em aterosclerose (LUQUE et al, 2013;LUQUE et al, 2015), e ainda foi mostrado que CD100 também é expressa em plaquetas, participando ora da formação de trombos, ora da recuperação da monocamada endotelial (ZHU et al, 2007). …”
Section: Cd100/sema4dunclassified
“…Interessantemente, vimos que apenas parte dos macrófagos de baço expressam CD100, sugerindo que essa molécula possa estar relacionada com subtipos específicos de macrófagos (LUQUE et al, 2013). Em um segundo trabalho, mostramos que CD100 e as plexinas, especialmente plexina B2, contribuem para a ligação de monócitos humanos a células endoteliais in vitro, e que essas duas células expressam CD100 na membrana, apontando para a proteína como um dos participantes na interação célula endotelial-monócito, um passo importante na aterogênese e formação de trombos (LUQUE et al, 2015).…”
Section: Cd100 Expresso Por Macrófagosunclassified